Effect of Wet Cupping Therapy on Reducing Pain in Patients with Low Back Pain in Bonto Bangun Work Area - Safruddin Yahya; Khaerul Mukrimin; Haryanti Haris (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Data from Public Health Center Bonto Bangun Bulukumba found that there were 93 patients experiencing LBP complaints from 2020, while in 2021 there were 71 patients and in 2022 from January to March there were 37 patients. Judging from the prevalence, from 2020-2022 it has indeed decreased but not yet resolved perfectly. Cupping therapy is a therapy recommended by the Prophet in which blood is extracted using a cup and a suction cup in the skin area which is incised 1 cm wide and 4 mm deep, so that it penetrates the epidermal layer of the skin, and because of the difference in pressure, the blood is pulled out of the peripheral blood vessels as much as 50-300 ml in 5 minutes and will cause a red or black rash. This series of therapies will eventually lead to healing as predicted by the Prophet Muhammad in his hadith with the permission of Allah ta'ala Research Objectives: To know the effect of wet cupping therapy on reducing pain in sufferers of Low Back Pain in the working area of Bonto Bangun, Bulukumba. The research design is true experimental. The sample is 16 people in the treatment group, and 16 people in the control group. The sampling technique is Simple Random sampling. The research was carried out in July 2022 in Bonto Bangun District, Bulukumba Regency. The results of the study are the pain scale before carrying out wet cupping therapy in the treatment group with a scale of 4.50 and the control group with a scale of 5.50. There was a difference in the pain scale after carrying out wet cupping therapy, namely in the treatment group it was 3.00 while in the control group it was 6.00. The results of the mean withney test obtained a value of p = 0.01 (smaller than the value of a = 0.05). There is a significant difference in pain scale between before and after doing wet cupping therapy. It is better for agencies to carry out routine wet cupping therapy programs and facilitate more LBP patients